Determination of microscopic parameters of quartz sand through tri-axial test using the discrete element method. (December 2017) - Cheng, Kuang; Wang, Yin; Yang, Qing; Mo, Yanbao; Guo, Ying
Abstract: A calibration procedure, in which coupled effects of microscopic parameters are considered, is proposed to determine the values of the microscopic parameters in the Discrete Element Method (DEM) for Fujian quartz sand. Laboratory tri-axial tests are conducted to be compared with the DEM simulations and the effects of end restraint in the laboratory tests are eliminated through a digital image measurement system. Sensitivities of the macroscopic behaviour of the specimen to the microscopic parameters are analyzed through DEM simulations. Four coupled effects of the microscopic parameters on the macroscopic behaviour are investigated through a graphic method and then considered in the calibration procedure.